Academic literacies twenty years on: a community-sourced literature review - John Hilsdon (Association for Learning Development in Higher Education (ALDinHE), 2019)
In 1998, the paper ‘Student writing in higher education: an academic literacies approach’ by Mary Lea and Brian Street reinvigorated debate concerning ‘what it means to be academically literate’ (1998, p.158). It proposed a new way of examining how students learn at university and introduced the term ‘academic literacies’. Subsequently, a body of literature has emerged reflecting the significant theoretical and practical impact Lea and Street’s paper has had on a range of academic and professional fields. This literature review covers articles selected by colleagues in our professional communities of the Association for Learning Development in Higher Education (ALDinHE), the association for lecturers in English for Academic Purposes (BALEAP), and the European Association of Teachers of Academic Writing (EATAW). As a community-sourced literature review, this text brings together reviews of wide range of texts and a diverse range of voices reflecting a multiplicity of perspectives and understandings of academic literacies. We have organised the material according to the themes: Modality, Identity, Focus on text, Implications for research, and Implications for practice. We conclude with observations relevant to these themes, which we hope will stimulate further debate, research and professional collaborations between our members and subscribers.